Formação de professores para educação em valores morais: construção de projetos em escola de ensino fundamental - Lima, Mayara Gama de (2021)
The general objective of this research was to investigate and describe an experience of teacher training in education on moral values in a school in the city of Vitória, its foundations in the municipal educational policy and the possibility for professionals to develop skills for the development of projects on the subject, in line with those that can be considered successful by authors in the field. Therefore, we developed three studies that will be presented in article format. In article 1, the documentary analysis of the continuing education policy for basic education professionals in Vitória (ES), indicated that it is based on legal and theoreticalconceptual assumptions. Themes about diversities were the main subjects worked on in the training actions. In article 2, we seek to carry out a diagnosis of the school context through interviews with 14 education professionals from an elementary education institution in the municipal network of Vitória (ES). The data indicated some points that need the attention of educators, such as: little involvement of families and the external community in school dynamics, physical infrastructure, lack of resources and administrative organization, integration of the teaching staff, and lack of an effective pedagogue and coordinator in the afternoon. The study also indicated that there are no intervention projects in the school aimed at work that, by providing and enhancing autonomy, address the conflicts and problems present in the institution. In article 3, in turn, we carried out an intervention, in the form of a training course carried out through workshops, which allowed the participating educators to elaborate an education project in values for the school. The qualitative analysis of the workshops and the project indicated aspects that are pointed out by the literature as necessary for education in moral values to be considered successful. (…)We observe, in this research, that it is necessary that the public authorities and the school administration invest in tools that make it possible to offer training courses on the subject, providing professionals, in addition, with the opportune time for these courses to be carried out within of the workload. Thus, interest in the subject alone will not be enough for teachers to continue in-service training, given the excessive workload that makes up their working conditions. Therefore, we suggest interventions that take place periodically in school spaces, that meet the needs of the school community and that contribute so that educators can reflect on their professional performance, especially with regard to the quality of school life and intervention in moral and ethical. Finally, we hope that this study can contribute to proposals for intervention in education in moral values, in a way that favors the construction of a society based on democratic coexistence, respect, solidarity and justice.